Variation of EFB-bicomponent fiber composition and its effect towards thermal resistivity and acoustical absorption as an air-conditioner ductwork inner insulation - Idris, Norain; Abdullah, Hasan Zuhudi; Rosli, Zulkifli Mohd; Zakaria, Muhammad Zulfattah; Idris, Maizlinda Izwana (2024)
Duct liner is utilized as a thermal insulation to avoid thermal loss from the cooled-conditioned airstream and as a sound insulation in air-conditioning systems. Usually, fiberglass is used as duct liners. However, its hazardous splints are carried together with the airstream into space and they are inhaled by occupants. They may affect human health, whereby they cause respiratory problems and even cancer, if it is inhaled for a long duration. Apart from fiberglass, closed-cell polyurethane (PU) and polyethylene (PE) are also utilized as duct liners, however, they are undoubtedly expensive and harmful out-gassing may occur after a certain period. Hence, another cheaper and safer duct liner alternative is developed by using natural fiber. A natural fiber composite made from palm oil waste, specifically empty fruit bunch (EFB), which is abundant, was used as the main material and a low melt bicomponent (bico) fiber, which was made of polyethylene (PE) and polypropylene (PP), was selected as a binder. Apart from that, the EFB-Bico fiber composite is also safer to humans than fiberglass as it uses natural fibers. Three samples A, B and C of the EFB fiber composite, which is 300mm x 300mm x 20mm in size, were prepared via hammer milling, electronic sieving, blending, press-forming and baking process, before its thermal and acoustic resistivity are tested. The density of the samples was set low at 150 kg/m3. Sample A contained 90 wt% of EFB and 10 wt% of bico, while sample B had 80 wt% and 20 wt% bico and sample C encompassed 60 wt% of EFB and 40 wt% of bico. The thermal resistivity or heat flow resistance of the three samples A, B and C were calculated after the value of their thermal conductivity were found via thermal conductivity test according to ASTM E1530. Meanwhile, the acoustic test was conducted with aid of an impedance tube kit (50 Hz - 6.4 kHz) type 4206 in accordance to ISO 10534-2 and ASTM E-1050-12. Among all samples, sample C showed the highest thermal resistivity, R-value and acoustic absorption coefficient, which was 0.341 W/m2°K due to the highest amount of PP/PE fiber and 1.0 sound absorption coefficient for higher frequency between 2200Hz and 3400Hz respectively. The R-value of sample C was however 46% lower than the thermal resistivity of fiberglass, which had R-value of 0.635 W/m2°K, even though its sound absorption coefficient was close to that of fiberglass. Therefore, it was found that the thickness of the samples need to be doubled from 0.02m to 0.04m to achieve the same R-value as fiberglass.